1975
DOI: 10.1111/j.1471-0528.1975.tb00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hyperbilirubinaemia Following the Use of Oxytocin in Labour

Abstract: Summary A prospective study of 1353 labours and the relevant newborn failed to reveal any significant difference between the incidence of neonatal hyperbilirubinaemia (defined as a level of 12 mg. or more per 100 ml.) following spontaneous labour, and after labour induced or accelerated by oxytocin. The incidence of unexplained neonatal hyperbilirubinaemia after spontaneous labour was 6.3 per cent. Following induced labour however there was a highly significant (P<0 00l) association between the mean total dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
4

Year Published

1977
1977
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 4 publications
1
13
1
4
Order By: Relevance
“…In recent years, there has been interest in the observation that there is an association be tween oxytocin or prostaglandins (E2 or F2u) used to induce labour in humans and neona tal hyperbilirubinaemia. While some workers have suggested that the use of oxytocin may be a causative factor [1,5,6], others have concluded no significant relationship [3,8]. Similarly, while Colder et al [4] reported an association between the total dose of PGE2 and the incidence of neonatal jaundice, this was refuted by Beazley et al [2].…”
Section: Introductioncontrasting
confidence: 39%
“…In recent years, there has been interest in the observation that there is an association be tween oxytocin or prostaglandins (E2 or F2u) used to induce labour in humans and neona tal hyperbilirubinaemia. While some workers have suggested that the use of oxytocin may be a causative factor [1,5,6], others have concluded no significant relationship [3,8]. Similarly, while Colder et al [4] reported an association between the total dose of PGE2 and the incidence of neonatal jaundice, this was refuted by Beazley et al [2].…”
Section: Introductioncontrasting
confidence: 39%
“…The use of oxytocin during labor has been a matter of great concern, especially in the Britishliterature, in regard to its alleged iatrogenic effect on the occurrence of neonatal hyperbilirubinemia [2,4,12]. Recent studies [3,5,7,11,13,18] cast doubt on the role of oxytocin per se in this respect, s neonatal hyperbiliruinemia seemed to occur predominantly in oxytocin induced labors s opposed to oxytocin accelerated ones following spontaneous-onset.…”
Section: Discussionmentioning
confidence: 97%
“…In a controlled retrospective study [4] the incidence of neonatal jaundice after oxytocin administration was 12.4 per cent äs compared to 8.1 per cent in a control group. BEAZLEY and ALDERMAN [2] have found a significant association between the mean total dose of oxytocin used for induction and the incidence of neonatal hyperbilirubinemia, suggesting a dose-dependent response. On the other hand GOULD et al [11] in a prospective study, failed to demonstrate an effect of maternal oxytocin infusion on neonatal serum bilirubin levels on the first and sixth days of life.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated neonatal hyperbilirubinemia in oxytocin-augmented labor [2,[15][16][17][18][19][20][21][22]. Previous studies have implicated administration of large volumes of electrolyte-free dextrose solutions together with oxytocin as an important factor contributing to hemolysis in the infant [23].…”
Section: Discussionmentioning
confidence: 99%